Multiphase non equilibrium pipe flow behaviors in the solid fluidization exploitation of marine natural gas hydrate reservoir. Issue 6 (21st November 2018) - Wei, Na; Sun, Wantong; Meng, Yingfeng; Liu, Anqi; Zhao, Jinzhou; Zhou, Shouwei; Zhang, Liehui; Li, Qingping
Abstract: In recent years, marine hydrate has attracted more and more attentions. As a creative way to efficiently exploit marine hydrate, the method of solid fluidization exploitation is to excavate and crush hydrate, transport hydrate particles to sea surface platform through airtight pipeline, and obtain methane gas finally. When hydrate particles are transported up, as temperature rises and pressure drops, hydrate will decompose at a certain critical position and produce a large amount of gas, bringing complicated gas‐liquid‐solid multiphase non equilibrium pipe flow, and seriously threating well control securities. Thus, we establish mathematical models of wellbore temperature and pressure, hydrate phase equilibrium, hydrate dynamic decomposition in riser pipe flow and wellbore multiphase flow coupling hydrate dynamic decomposition, and propose and verify numerical calculation method. Then numerical model application analysis under different construction parameters is carried out, influence behaviors of multiphase non equilibrium pipe flow are obtained, and field construction measures are put forward. Properly increasing solid throughput can increase production of natural gas. However, problems such as well control risks will intensify. Therefore, delivery capacity, liquid density, and wellhead back pressure should be increased appropriately at the same time. This study provides important technical support for solid fluidization exploitation of marine hydrate. Abstract : Physical model and system mathematical models are established to demonstrate multiphase non equilibrium pipe flow in hydrate solid fluidization exploitation of marine natural gas hydrate. Numerical calculation methods for multiphase non equilibrium pipe flow is developed and verified. Numerical model is applied to analyze and obtain the multiphase non equilibrium flow behaviors in hydrate solid fluidization exploitation.